Beyond birth weight: The origins of human capital - Gabriella Conti; Mark A. Hanson; Hazel Inskip; Sarah Crozier; Cyrus Cooper; Keith Godfrey (Institute for Fiscal Studies (IFS), 2018)
Birth weight is the most widely used indicator of neonatal health. It has been consistently shown to relate to a variety of outcomes throughout the life cycle. Lower birth weight babies have worse health and cognition from childhood, lower educational attainment, wages, and longevity. But what's in birth weight? What are the aspects of the prenatal environment that birth weight actually reflect? In this paper we address this fundamental, yet currently unanswered, question, using unique data with fetal ultrasound measurements from two UK sources. We show that birth weight provides a distinctly limited picture of the uterine environment, capturing both positive and negative aspects of fetal health. Other newborn measures are more informative about different dimensions of the prenatal environment and more predictive of child growth and cognitive development, beyond birth weight. Additionally, patterns of fetal growth are predictive of child physical and mental health conditions, beyond health at birth. Our results are robust to correcting for measurement error, and to accounting for child- and mother-speci c unobserved heterogeneity. Our analysis rationalizes a common finding in the early origins literature, that prenatal events can influence postnatal development without affecting birth outcomes. It further clari es the role of birth weight and height as markers of early health, and suggests caution in adopting birth weight as the main target of prenatal interventions.
Keywords: 330; Birth Weight; Fetal Development; Prenatal Investments; Developmental Origins of Health